International Joint Ventures in India: Motives of Australian Firms - An Exploratory Study through Resource Based Approach - Sharma, Rajeev D (Indian Journal of Marketing, 2007)
There is a long tradition in marketing literature to study the ’motives’ of IJV formation in different country contexts using different theoretical perspectives including transaction cost analysis and strategic management approach. The key objective of this paper is to investigate the motives of international joint ventures (IJV) formation of Australian firms in India. Despite the abolition of the legislative necessity for almost a decade, the IJV remains the most popular form of governance structure in India. The paper investigates the IJV motives using the resource-based view (RBV) of the firm. The empirical results of the RBV approach shed new light on specific resource seeking motives of Australian IJV parent firms in India. It provides evidence that seeking intangible resources is generally more important to Australian respondents than seeking tangible resources.